The Phenomenon of Political Participation Apathy: Analysis of Voter Turnout Decline in the 2024 Regional Head Elections of Cirebon Regency - Nadya Tridrisna Manurung; Sunoto Sunoto (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
This study analyzes the phenomenon of declining voter participation in the 2024 Cirebon Regency Regional Head Elections (Pilkada). This phenomenon is of concern because political participation is an important indicator of the quality of local democracy. The purpose of this study is to identify the factors causing the decline in participation and to analyze its implications for the democratization process at the regional level. Using a qualitative method with a descriptive approach, this study involved various elements of society, such as religious leaders, village officials, youth, students, and election organizers. Data were collected through field observations and in-depth interviews with key informants, then analyzed thematically to find patterns and meanings behind the phenomenon. The results show that the decline in voter participation is influenced by a combination of structural and cultural factors, including low political awareness, increased population mobility, the policy of regrouping polling stations (TPS), and growing apathy towards local politics. Young voters and urban communities tend to be indifferent due to a lack of political literacy and disappointment with regional head candidates who are considered to bring no change. The regrouping of polling stations, which increases the number of voters per location, also reduces the convenience and effectiveness of voting. These findings imply the need for strategies to increase participation through continuous political education, innovation in voting systems that are adaptive to citizen mobility, and political campaigns based on concrete ideas and programs to restore public trust in the democratic process.Keywords: political participation, regional elections, Cirebon, apathy, local democracy.